Expression of toll-like receptor-2 and -4 in amniochorion membranes of preterm delivery in the presence of histologic chorioamnionitis - Moço, Natália Prearo [UNESP]; Martin, Laura Fernandes [UNESP]; Polettini, Jossimara [UNESP]; Pereira, Ana Carolina [UNESP]; Peraçoli, José Carlos [UNESP]; Silva, Márcia Guimarães da [UNESP] (Scientific Research Publishing, 2014)
Expression of Toll-like receptors at the maternal-fetal interface during normal and complicated pregnancies has aroused interest in the last few years. However, despite the importance of TLR-2 and TLR-4, which recognizes most microorganisms presenting in the amniotic cavity infections associated with prematurity, comparison of the expressions of these receptors is rare in the literature. Thus, the purpose of this study was to compare the gene expression between TLR-2 and TLR-4 in amniochorion membranes of pregnant women with preterm delivery in the presence of histologic chorioamnionitis (HCA). Amniochorion membranes were collected from 40 pregnant women with preterm delivery; 20 presented HCA and 20 did not. Fragments of the membranes were submitted to total RNA extraction, followed by cDNA production by reverse transcription. Real time quantitative PCR was used to quantify the gene expression of the TLRs. mRNA concentrations between TLR-2 and TLR-4 were compared using the nonparametric Mann-Whitney test. TLR-2 expression was higher than TLR-4 expression in the presence of HCA. No difference was observed between TLR-2 and TLR-4 expression in membranes in the absence of inflammatory infiltrate. In conclusion, amniochorion membranes express TLR-2 and TLR-4 and higher TLR-2 expression in the presence of histologic chorioamnionitis suggests that microorganisms recognizable by TLR-2 play an important role in the physiopathology of preterm labor.
Keywords: Preterm labor; Pregnancy complications; Innate immunology; TLR-2; TLR-4